O papel do guanxi na superação da distância psíquica e o impacto na performance exportadora - Soares, Soraya de Souza (2022)
With the general objective of analyzing how guanxi can minimize the psychic distance barriers that impact the export performance between Brazil and China. The study was guided by the following specific objectives: To verify if there is a relationship between psychic distance barriers and the export performance of Brazilian companies in their commercial relationship with China; Identify whether there is a positive influence between companies that perform guanxi and export performance; Describe how the formation of guanxi occurs by the companies surveyed and Identify the motivations for commercial partnerships between Brazil and China. Through a descriptive study and a qualitative approach, the research was analyzed based on content analysis having as a strategy the use of multiple case studies focusing on agribusiness, three managers of meat exporting companies to China were interviewed , plus ten Chinese trading experts. With this, it was possible to observe that the three constructs: psychic distance, guanxi and export performance are connected, making it clear that doing business within one's own country is challenging, and requires a series of issues both internal and external, therefore, seeking internationalization in a country as different in cultural matters as China is, requires a lot of preparation from interested parties, and the search for partnerships and support is one of the means to be followed. In order to overcome psychic distance barriers, guanxi is essential for successful relationships with the Chinese, as it is a necessary social skill in China, with regard to social, political and organizational functioning. It can be seen that knowing about guanxi is a factor that helps in relationships and negotiations, even as profit comes in some cases, in the first place, at least having a well-established guanxi positively influences the time of negotiations, regardless of the size of the company. company, administrative advantages can be acquired through guanxi. Thus, it was found that issues related to export performance are part of the concerns of entrepreneurs, and are also considered by specialists. It was noticed that the performance stems from the specific issues of doing business with China (and its peculiarities), but that also concern the nature of international business, and are not exclusive to the relationship with China. When relationships are well established and the product is well received in the country of destination, profit and representativeness through exports are achieved, making export performance satisfactory, both in terms of financial and strategic performance, resulting in an overall positive satisfaction.